2014
DOI: 10.1159/000365397
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Targeted MRI-Guided Biopsy with Systematic Transrectal Ultrasound-Guided Biopsy in Patients with Previous Negative Prostate Biopsies

Abstract: Objective: To directly compare the diagnostic performance of targeted MRI-guided biopsy (MR-GB) and systematic transrectal ultrasound-guided biopsy (TRUS-GB). Methods: Thirty-five patients with at least one negative TRUS-GB, persistently elevated or rising prostate-specific antigen and a lesion suspicious for prostate cancer (PC) on multiparametric MRI (mpMRI) scored by using the Prostate Imaging Reporting and Data System (PI-RADS) were included. A median of three targeted biopsies per lesion were obtained and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…MRI is the most accurate imaging modality for the localization of PCa, the only clinical imaging method that depicts the zonal anatomy of the prostate in detail [24]. When PB is targeted to MRI-detected lesion, the diagnosis of PCa and the percentage of significant PCa focus increase [25,26]. van den Bos et al [3] recommends the inclusion of MRI before considering the FT, due to the high negative predictive value (up to 95%) for clinically significant tumours [27].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the most accurate imaging modality for the localization of PCa, the only clinical imaging method that depicts the zonal anatomy of the prostate in detail [24]. When PB is targeted to MRI-detected lesion, the diagnosis of PCa and the percentage of significant PCa focus increase [25,26]. van den Bos et al [3] recommends the inclusion of MRI before considering the FT, due to the high negative predictive value (up to 95%) for clinically significant tumours [27].…”
Section: Discussionmentioning
confidence: 99%
“…The patient also needs to be informed about the increased risk of a PSM if there is inadequate information from the prostate biopsy. Emerging techniques, including MRI for staging and MRI-targeted biopsies, may lead to a more accurate localization of cancer foci and help to reduce the risk for a PSM [27,28]. Unless these techniques become the standard of care, attempts should be made to establish rigid guidelines to further improve the quality of conventional prostate biopsies and their reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were seen in another study of men with prior negative biopsy and elevated PSA. Kaufmann et al found that cancer detection rate was 20 % higher with fusion biopsy and all cancers identified by targeted biopsy met the criteria for significant cancer [30]. The ability of mp-MRI to identify significant cancer in men with prior negative biopsies was studied.…”
Section: Prior Negative Biopsymentioning
confidence: 99%